Performance Analysis of a PEMFC-Based Grid-Connected Distributed Generation System - Akpolat, Alper Nabi; Dursun, Erkan; Yang, Yongheng (Applied sciences, 2023)
Less energy consumption and more efficient use of renewables are among the sustainable energy targets of modern societies. The essential activities to be achieved under these objectives are to increase distributed generation (DG) structures’ applicability. DG systems are small-scale versions of the traditional power grid; they are supported by micro turbines, photovoltaics (PV) modules, hydrogen fuel cells, wind turbines, combined heat and power systems, and energy storage units. The aim of this research is to detail the performance analysis of a proton-exchange membrane fuel cell (PEMFC)-based grid-connected distributed generation system with the help of empirical calculations. To this end, we aimed to establish the system and analyze the performance of the reliable operation of the system with experimental verifications. The findings demonstrate how much power can be generated annually, through real meteorological data, to dispatch to constantly variable loads. While 53.56% of the total energy demand is met by the utility grid, 46.44% of the demand is met by the produced energy i.e., from the DG. The PEMFC-based DG system analyzed in detail in this study was located at Marmara University. According to the results of the performance analysis, significant points of this study will be highlighted to assist the researchers working in this field. Our results are encouraging and can be certified by a larger sample size with neat weather conditions in terms of the percentage of procurement of energy.